Discovery of a new genus and new species of Indo-West Pacific pilumnoidid crab from a semisubmersible oil platform (Crustacea: Brachyura: Pseudozioidea) - Ng, Peter K. L.; Ahyong, Shane T. (Zootaxa, 2013)
A new genus and new species of pseudozioid crab of the family Pilumnoididae is described from a fouling community on a semisubmersible oil platform in Singapore that had been operating in the Timor Sea and South China Sea. Setozius in-certus gen. et sp. nov. superficially resembles species of Pilumnus (Pilumnidae, Pilumnoidea) but has male first and sec-ond gonopod structures characteristic of the Pseudozioidea. The form of the carapace, male anterior thoracic sternum and male abdomen indicates that it should be classified in the Pilumnoididae. Setozius is the first member of the family to be recorded from the Indo-West Pacific; all other known pilumnoidids occur in the Atlantic and eastern Pacific.